The Relevance of John Locke’s Thoughts to the Development of Empiricism-Based History Learning in the Era of Independent Learning - Ismaul Fitroh; Muhammad Abror Amanullah; Rendy Wahyu Satriyo Putro; Ika Rahmatika Chalimi (Journal of General Education and Humanities, 2026)
This study examines the relevance of John Locke’s empiricism as a philosophical foundation for developing contextual and reflective history learning in the era of Merdeka Belajar. The research responds to the persistent dominance of memorization-oriented history learning, which limits students’ critical thinking and historical awareness despite contemporary educational demands that emphasize active, student-centered learning. This study aims to analyze how Locke’s concepts of tabula rasa, sensation, and reflection contribute conceptually to the development of inquiry-oriented and meaningful history learning. The study employed a qualitative, philosophical library research approach, using Locke’s major philosophical works as primary sources and contemporary literature on the philosophy of education, history education, inquiry learning, and Merdeka Belajar as secondary sources. Data analysis was conducted through data reduction, conceptual categorization, interpretive analysis, and constructive synthesis. The findings indicate that Locke’s empiricism strengthens the ontological, epistemological, and axiological foundations of history learning by emphasizing evidence-based reasoning, reflective inquiry, and active knowledge construction. The study also finds that empiricism-based learning supports inquiry-based, project-based, and authentic-source analysis, as well as reflective assessment practices relevant to the objectives of Merdeka Belajar. Therefore, Locke’s empiricism provides both a conceptual contribution to the philosophy of history education and practical implications for developing more critical, contextual, and meaningful history learning in contemporary Indonesian education.